Analysis of the use of the Miftah Lil Ulum Method in Learning the Kitab Kuning for Children - Moh Syakur; Hasmi Hashona (TA'DIBUNA: Jurnal Pendidikan Agama Islam, 2022)
As the oldest educational institution in Indonesia, one of the characteristics of Islamic boarding schools is the implementation of studies on Islamic religious sciences based on Arabic books compiled in the Middle Ages, better known as the kitab kuning (kutub at-turats). The Miftah Lil Ulum method is one of the many methods that offer the convenience of students to understand the contents of the kitab kuning. By providing interesting packaged material to be remembered by the students. In exploring the success of this method at the Diniyyah Raudlatus Shalihin madrasah, researchers used qualitative methods which intended to understand phenomena about what was experienced by research subjects, for example, behaviors, perceptions, motivations, and actions. This research seeks to reveal how Madrasah Diniyyah Raudlatus Shalihin teaches the Miftah Lil Ulumt method as an alternative method of learning Arabic to understand the Kitab kuning.